(3EOGQI GdJCejf aj YGde GdCYeGds - (3TQja(B, (3aJM Gddgs ((3GdEScfOQjI(B:s (3ecJHI heWHYI GdETYGY GdafjI(B,s, 2006)
(3CSQGQ GdfLGM aj UfGYI GdJCejf(B-(3cja JVY KhQI aj YGde GdJCejfs
Keywords: (3GdCYJQGVGJs; (3GdEcJTGas; (3GdJCejf (B- (3GdHfhcs; (3GdYQhVs; (3bhGYO GdHjYs